Exomella Casey, 1914 - eine amphipazifisch disjunkte Gattung mit der Beschreibung einer neuen Art aus der Sikhote-Alin-Kette im Fernen Osten Rußlands (Coleoptera: Byrrhidae). (Beiträge zur Kenntnis ostpaläarktischer Insekten; 2.) - Pütz, Andreas; Lafer, German Shlemovich; Zerche, Lothar (Contributions to Entomology = Beiträge zur Entomologie, 1995)
The first Palaearctic species of Exomella Casey, 1914, a genus previously known to contain only two species from the Western Nearctic region (Washington, Oregon, Idaho, British Columbia), is described from the Sikhote-Alin mountain range in the Russian Far East: Exomella sikhotealinensis sp. n. Both the new species and the Nearctic species Exomella pleuralis (Casey, 1908) and Exomella merickeli Johnson, 1985, are illustrated; ecological, phenological and zoogeographical data as well as a diagnostic key are provided. The relationships between the Nearctic and the Palaearctic species are discussed, and the phylogenetic system of the genus is presented. Lioon simplicipes (Mannerheim, 1852), presumably the sister group, is included in the study. The tribe Exomini Casey, 1912, is revalidated. The phylogenetically old monophylum Exomella is an example of a group of Asiamerican origin. The Catopocerinae (Coleoptera, Leiodidae) and some members of the Grylloblattida and the Blattoidea represent similar examples of such origin and recent distribution. Nomenclatural Acts sikhotealinensis Pütz &Lafer, 1995 (Exomella), spec. n.